Além da pele: o corpo de antes e o que se fabrica a cada dia. Memórias, trama de desejos e práticas de homens trans. - Oliveira, Adelaide Suely de (2023)
This doctoral thesis intends to comprehend the trans men's experience in the process of male body fabrication, overpassed by discourses about masculinity and how these bodies are articulated in relationship to their new gender identity. This research is inserted in the field of post-structuralism studies, having as an analytical mark gender, race and decolonization, based on the Queer Theory and the Subaltern Studies. It is a study inserted on the field of social networks website uses, having an online approach. Its specific objectives are: understanding the uses of internet and social networks as a space for reflection over trans masculinity and comprehending how trans men are self-subjectifying at the current political moment, which main phenomena overpass them and which effects are produced upon them. It is a qualitative research realized through computer networks, using the Youtube platform. Six trans men were studied, with age variation between 21 and 25 years, Brazilians, from the Northeast, Southeast, South and Midwest regions. Four of them define themselves as white and two of them define themselves as black. On the video sharing platform, these trans men are creating a space for reflection, a place for meetings in which they talk to other trans men about matters related to transgenderity and they tell how they are self-subjectifying as men, speaking about their masculinities from the narratives they use in the weekly posts. The thesis demonstrates that all people fabricate their bodies in order to suit a gender, building or rebuilding these bodies, whether equal or different from the sex they were designated from birth. It is not, therefore, something exclusive to trans people the search for adaptation to a gender. Cis people or trans are the result of a production - they are fabricated, created and artificial. A fiction, a creation that is made and remade daily, all determined by a compulsory system in which we are dipped and drowned without even taking account.